Trypanosoma brucei gambiense Infections in Mice Lead to Tropism to the Reproductive Organs, and Horizontal and Vertical Transmission. - Nicolas Biteau; Corinne Asencio; Julien Izotte; Benoit Rousseau; Muriel Fèvre; Davita Pillay; Théo Baltz (Public Library of Science (PLoS), 2016)
Trypanosoma brucei gambiense, transmitted by the tsetse fly, is the main causative agent of Human African trypanosomosis in West Africa and poses a significant health risk to 70 million people. Disease progression varies depending on host immunity, but usually begins with a haemo-lymphatic phase, followed by parasite invasion of the central nervous system. In the current study, the tropism of T. b. gambiense 1135, causing a low level chronic 'silent' infection, was monitored in a murine model using bioluminescence imaging and PCR. A tropism to the reproductive organs, in addition to the central nervous system, after 12-18 months of infection was observed. Bioluminescent analysis of healthy females crossed with infected males showed that 50%, 62.5% and 37.5% of the female mice were subsequently positive for parasites in their ovaries, uteri and brain respectively. Although PCR confirmed the presence of parasites in the uterus of one of these mice, the blood of all mice was negative by PCR and LAMP. Subsequently, bioluminescent imaging of the offspring of infected female mice crossed with healthy males indicated parasites were present in the reproductive organs of both male (80%) and female (60%) offspring. These findings imply that transmission of T. b. gambiense 1135 occurs horizontally, most probably via sexual contact, and vertically in a murine model, which raises the possibility of a similar transmission in humans. This has wide reaching implications. Firstly, the observations made in this study are likely to be valid for wild animals acting as a reservoir for T. b. gambiense. Also, the reproductive organs may act as a refuge for parasites during drug treatment in a similar manner to the central nervous system. This could leave patients at risk of a relapse, ultimately allowing them to act as a reservoir for subsequent transmission by tsetse and possibly, horizontally and vertically.